DEVELOPING A MEASUREMENT SCALE FOR ASSESSING THE EFFICIENCY OF TAX ADMINISTRATION AMONG OIL AND GAS COMPANIES IN NIGERIA (Malaysian Management Journal, 2020)
Inefficient tax system causes the government to lose a huge amount of revenue. Tax administrators are primarily responsible for collecting taxes due from taxpayers following the relevant tax laws and regulation in a way that instils confidence on taxpayers through efficient tax administration. This paper aims at validating relevant and reliable measurement scale for assessing the effectiveness of tax administration efficiency in dealing with oil and gas companies operating in the Nigerian oil sector. Hence, an adapted questionnaire comprising four items was administered on 300 local and multinational oil and gas companies in Nigeria. All the items were subjected to evaluations and validations by eight experts’ reviewers with cognate experience in oil and gas activities. Evaluation of reliability and validity of the measures of tax administration efficiency was performed through Confirmatory Factor Analysis (CFA) using SPSS version 25 and Smart PLS version 3.8. The results provide evidence that the proposed tax administration efficiency scale attained reliability and validity criteria. Consequently, Policymakers, practitioners and researchers can adapt this scale to assess the effectiveness of tax administration efficiency by companies in different jurisdictions across the globe. This study expands existing literature and contributes new ideas to the subject area. By implication, the validated scale will assist oil and gas producing countries to come up with policies that ensures efficiency in tax administration and increase government revenues.